DUH 2000 the millennium bug problem of banks in Iloilo City - Alpos, Azenneth Ravena; Duco, XZ Cabardo; Guevarra, Cherlie Rose Gapanayao; Santiago, Frances Joy Fernandez; Trinidad, Imelda Toremo
Using a questionnaire-interview method, sixty-four banks were subjected to the study to determine their awareness, fears and anxieties regarding the Y2k bug. Also, the researcher wanted to know if the compliant systems of the bank will work and if the Y2K bug will have an effect in their business. After proper analysis and application of appropriate statistical treatment on the data obtained from the study, the researchers were able to prove that the banking industry was prepared to face the Y2K compliant system. The managers were well equipped in combating the bug as tested on their Y2K compliant system. Furthermore, the study proved that the Y2K bug has no effect on the banking system, that it was a big hoax and that there was no significant difference in the perception of managers about the Y2k when classified according to their gender, age and religion. In view of this, the researchers suggest that the managers should continue to be aware of things and events that is happening in the industry. Also, they should be ready when another event like this will shake the banking industry of Iloilo City. Iloilo City should continue its responsiveness as tested during the millenium bug issue. The media helped a lot in informing the public about the bug but they also caused panic and the managers believed that it was the media's fault why a lot of their clients withdrew their money before January 1, 2000. They should continue informing the public about pressing issues but not to the point of causing panic.